Effectiveness of gargling with 100% coconut oil to prevent plaque accumulation and gingival bleeding - Soulissa, A. G.; Juslily, M.; Juliawati, M.; Lestari, S.; Ramli, N. P.; Albert, Albert; Ismail, Azlini (CRC Press, Taylor & Francis Group, 2024)
Background: Based on Indonesian Baseline Health Research (Riskesdas) conducted in 2018, 67.8% of Indonesians suffer from periodontal diseases. Gingivitis is marked by inflammation, bleeding, and swelling of the gums due to plaque buildup. While chemical agents can be effective in managing plaque, natural materials like coconut oil are worth considering. Coconut oil contains lauric acid, which has been shown to have anti-inflammatory and antimicrobial properties. Objectives: To investigate the efficacy of coconut oil as mouthwash in reducing gingivitis. Methods: A clinical study was conducted using a pre-post test control group design. Thirty participants with plaque-induced gingivitis were selected and distributed randomly into the experimental group (n=20) and control group (n=10). The experimental group was asked to rinse with coconut oil 100% and the control group was asked to rinse with 0.1% chlorhexidine mouthwash for 15 mL in 30s. The OHI-S and PBI scores were used to assess plaque accumulation and gingival bleeding at baseline on the 10th day. Data were analyzed using paired t-tests and independent t-tests. Results: After 10 days of treatment, both the experimental and control groups demonstrated a significant decrease in the mean OHI-S and PBI scores. However, there was no significant difference in the reduction of OHI-S and PBI scores between the two mouthwashes. Conclusion: The result of the study demonstrates using coconut oil as mouthwash can effectively decrease plaque accumulation and gingival bleeding. As a natural product, coconut oil can be used as an additional oral hygiene practice for individuals with gingivitis.